The effectiveness of gas supply system for high-rise residential building / Munira Mansor - Mansor, Munira (2001)
Nowadays, gas has become one of the important raw energy supply in almost every field. Currently, gas has been developed as one of the energy supply for residential. At first, it is adapted in industrial sector but parallel with the economic development in Malaysia, gas supply system has been used for residential sector too. This proves that gas can be used commercially, whether for industrial sector or residential sector. Gas supply system for high-rise residential buildings in Malaysia, comes in two types. However, only recently, gas supply system for cooking purposes is adapted for high-rise building. Since then, many high-rise residential buildings adopted this system as part of the services offer for the residence. This is the reason why case studies on both systems is being done, in order to know which gas system is more efficient to cater the total numbers of residence living in one block of theb high rise building. As a matter of fact, other considerential factors on the selection of gas supply system for high-rise buildings and the effectiveness of such systems are being highlighted and studied too. In Malaysia, the authority has setup guidelines for gas consumption which are known as SIRIM MS 830 and Gas Supply Act 1993. Both of these guidelines stat the terms and conditions for gas supply method and installation in whatever field or sector that adapted this energy.